Search for the inelastic scattering of weakly interacting massive particles on the 178m2Hf isomer - Vladimir Kirischuk; Valeriy Didkovskiy; Sergei Drapey; Volodymyr Tretyak; Sergei Kirischuk (Physics Letters B)
The results of the second experimental search for dark matter using the 178m2Hf isomer are presented. The high-energy γ-rays that cannot be emitted during the spontaneous decay of this isomer but might arise from the population of excited nuclear levels in 178Hf due to the inelastic scattering with dark matter particles are analyzed in detail. The limits on the half-life of the dark-matter-induced transitions, obtained from limits on these γ-ray intensities, have reached T1/2 > 9.3 × 105 years. Further progress of such experimental efforts is discussed.